AN EXPLORATORY STUDY ON EMPLOYEE’S PERCEPTION TOWARDS LEAN MANUFACTURING SYSTEMS - Rajesh Kumar MEHTA; Dharmendra MEHTA; Naveen K Mehta (Management & Marketing)
Lean deals with generating more value for customers by eliminating factors that are merely considered waste. Lean Manufacturing is a systematic approach to identifying and eliminating waste through continuous improvement. Lean Manufacturing uses less of everything and attains its set objectives by excellent teamwork, communication, and competent use of available resources & continuous Improvement. The present paper is an attempt to study employee’s perception towards lean manufacturing systems in gear industry.